Facial emotion recognition in adolescent depression: The role of childhood traumas, emotion regulation difficulties, alexithymia and empathy - Hesna Gul; Yasemin Tas Torun; Fatma Hulya Cakmak; Ahmet Gul (Indian Journal of Psychiatry)
Introduction: Facial emotion recognition (FER) is crucial for effective social competency, and problems in this skill are linked depression during adolescence. In this study, we aimed to find the rates of FER accuracy for negative (fearful, sad, angry, disgusted), positive (happy, surprised), and neutral emotions, and the possible predictors of FER skill for most confusing emotions. Subjects and Methods: A total of 67 drug-naive adolescents with depression (11 boys, 56 girls; 11–17 years) were recruited for the study. The facial emotion recognition test, childhood trauma questionnaire and basic empathy, difficulty of emotion regulation, and Toronto alexithymia scales were used. Results: The analysis demonstrated that adolescents have more difficulties in recognizing negative emotions when compared the positive ones. The most confusing emotion is fear (39.8% of fear was recognized as surprise). Boys have lower fear recognition skill than girls and higher childhood emotional abuse, physical abuse, emotional neglect, and difficulty in describing feelings to predict lower fear recognition skill. For sadness recognition skill, emotional neglect, difficulty in describing feelings, and depression severity were the negative predictors. Emotional empathy has a positive effect on disgust recognition skill. Conclusion: Our findings demonstrated that impairment of FER skill for negative emotions is associated with childhood traumas, emotion regulation difficulties, alexithymia, and empathy symptoms in adolescent depression.